Evaluation of gamification as a tool for open access publishing among researchers: insights from a conjoint analysis - Mazarakis, Athanasios; Bräuer, Paula; Dorsch, Isabelle (Scientometrics, 2025)
The recent developments in the scientific system have been characterized by an increasing openness, with open access (OA) publishing emerging as a central principle. OA represents an alternative model for publishing research articles, diverging from the traditional subscription-based model. While positive developments have been observed, obstacles for OA remain, including elevated publication costs and the imperative to publish at the highest level in the scholarly community with a significant impact. To overcome these obstacles, it may be beneficial to consider using non-monetary incentives, such as gamification, to promote OA publishing. To address this challenge, an experimental study employing a conjoint analysis has been conducted to investigate the impact of various gamification options on researchers' publishing behavior. The study utilized a sample of N = 356 subjects. The results demonstrate that the Journal Impact Factor (JIF) is a dominant criterion for determining where to publish. However, gamification, particularly in the form of badges associated with an article, can also significantly influence journal selection and support OA. Additionally, qualitative data was collected to identify other factors influencing the choice of a journal for OA from the perspective of the participating researchers in the experiment.